Composite electrolyte, method for preparing same, and lithium secondary battery comprising same
By using a composite electrolyte of liquid electrolyte and large-particle oxide solid electrolyte particles in lithium secondary batteries, the problems of liquid leakage and insufficient mechanical properties are solved, excellent ion conductivity and safety are achieved, and lithium secondary is improved. Overall performance of the secondary battery.
Patent Information
- Application Number
- CN202380037999.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-20
- Filing Date
- 2023-09-21
- Publication Date
- 2024-12-13
AI Technical Summary
The liquid electrolytes in existing lithium secondary batteries have problems of liquid leakage and insufficient mechanical properties, and insufficient ion conductivity, which affects safety and performance.
Using a composite electrolyte containing liquid electrolytes, crosslinked polymers with curable functional groups and oxide solid electrolyte particles with particle size greater than 300 nm, the thermal curing method is prepared to avoid separate separation membranes and optimize oxide solid electrolytes. The particle size and content of the particles are used to improve ion conductivity.
It achieves excellent mechanical properties and ion conductivity without using a separate separation membrane, reduces the risk of liquid leakage, and improves the safety and electrical characteristics of lithium secondary batteries.
Smart Images

Figure CN119137782A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0132212 filed on October 14, 2022, and Korean Patent Application No. 10-2023-0125560 filed on September 20, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present disclosure relates to a composite electrolyte exhibiting improved mechanical properties and ion conductivity while preventing liquid leakage, a preparation method thereof, and a secondary battery including the same. Background Art
[0004] Recently, with the rapid popularization of electronic devices such as mobile phones, laptops, electric vehicles, etc. using batteries, the demand for miniaturized, lightweight and relatively high-capacity secondary batteries has increased rapidly. In particular, lithium secondary batteries are lightweight and have high energy density, so they are of interest as driving power sources for portable devices. Therefore, in order to improve the performance of lithium secondary batteries, research and development work is being actively carried out.
[0005] Such lithium secondary batteries, such as lithium ion batteries, generally have a structure in which a separation membrane is inserted between a positive electrode and a negative electrode composed of an active material capable of inserting and extracting lithium ions, and a liquid electrolyte is filled. However, in the case of lithium ion batteries, since they contain a liquid electrolyte, liquid leakage is likely to occur during charging / discharging or use, and there is a high risk of fire or explosion, which has become a major problem.
[0006] In recent years, solid electrolytes have been actively developed to improve the safety of lithium secondary batteries, and as one of them, polymer solid electrolytes are being studied. However, such polymer solid electrolytes themselves exhibit lower ion conductivity than liquid electrolytes, and therefore, the use of liquid electrolytes such as composite electrolytes containing lithium salts and organic solvents in polymers is more widely considered.
[0007] However, even in the case of such existing composite electrolytes, there is still a possibility of liquid leakage during the manufacture or use of the battery, or there is a disadvantage of insufficient mechanical properties. In addition, there is a problem that a separation membrane is inevitably required to support the composite electrolyte, and such existing composite electrolytes do not show sufficient ion conductivity, so it is necessary to improve these points. Summary of the invention
[0008] [Technical issues]
[0009] An object of the present disclosure is to provide a composite electrolyte and a method for preparing the same, the composite electrolyte exhibiting improved mechanical properties and ion conductivity while preventing liquid leakage.
[0010] Another object of the present disclosure is to provide a secondary battery, which includes the composite electrolyte and thus exhibits improved electrical characteristics and safety.
[0011] [Technical solution]
[0012] According to one aspect of the present disclosure, there is provided a composite electrolyte comprising:
[0013] Liquid electrolytes;
[0014] a cross-linked polymer of a monomer having a curable functional group; and
[0015] The oxide-based solid electrolyte particles are dispersed on the cross-linked polymer and have a particle size greater than 300 nm.
[0016] According to another aspect of the present disclosure, a method for preparing the above-mentioned composite electrolyte is provided, the method comprising the following steps: forming a composition on a substrate, the composition comprising a liquid electrolyte, a monomer having a curable functional group, and oxide-based solid electrolyte particles having a particle size greater than 300 nm; and thermally curing the monomer of the composition at above 60° C. in the presence of an initiator.
[0017] According to another aspect of the present disclosure, a lithium secondary battery is provided, which includes: a positive electrode containing a positive electrode active material; a negative electrode containing a negative electrode active material; and a composite electrolyte interposed between the positive electrode and the negative electrode.
[0018] Now, a composite electrolyte according to a specific embodiment of the present disclosure, a preparation method thereof, a secondary battery including the same, and the like will be described.
[0019] A composite electrolyte according to an embodiment of the present disclosure includes: a liquid electrolyte; a cross-linked polymer of a monomer having a curable functional group; and oxide-based solid electrolyte particles dispersed on the cross-linked polymer and having a particle size greater than 300 nm.
[0020] The composite electrolyte of one embodiment includes a cross-linked polymer obtained by curing a monomer having a curable functional group (ethylenically unsaturated bond, etc.) by a method such as thermal curing, and also includes a liquid electrolyte contained in such a cross-linked polymer, and oxide-based solid electrolyte particles dispersed on the cross-linked polymer and having a particle size greater than 300 nm, or 310 to 800 nm, or 350 to 600 nm.
[0021] Since the composite electrolyte of one embodiment includes a liquid electrolyte, such as an electrolyte solution containing a non-aqueous organic solvent and a lithium salt, within the cross-linked structure of a cross-linked polymer, it can exhibit excellent mechanical properties without even requiring a separate separation membrane that can minimize the occurrence of fire or the like due to leakage of the liquid electrolyte or the like.
[0022] In addition, it has been found that oxide solid electrolyte particles, particularly oxide solid electrolyte particles having an optimized particle size and / or content range, are further contained in a cross-linked polymer, thereby being able to exhibit more improved ionic conductivity. It is predicted that this is because the particle size and content of the oxide solid electrolyte particles are optimized so that these particles can be more evenly dispersed in the cross-linked polymer and the liquid electrolyte. As a result, the ionic conductivity can be maximized due to the liquid electrolyte and the oxide solid electrolyte particles, and the ionic conductivity of the composite electrolyte of an embodiment can be further improved.
[0023] On the other hand, the liquid electrolyte contained in the cross-linked polymer may include a non-aqueous organic solvent and a lithium salt. This non-aqueous organic solvent remains liquid in the cross-linked structure of the cross-linked polymer, or a portion thereof may solidify together with the cross-linked polymer, thereby further improving the mechanical properties of the composite electrolyte. Such a non-aqueous organic solvent may dissociate the lithium salt in the cross-linked polymer and act as an ion transport medium. Therefore, this liquid electrolyte is contained in the cross-linked polymer, so that the composite electrolyte can show excellent ion conductivity compared with a solid polymer solid electrolyte.
[0024] The type of nonaqueous organic solvent that can be used herein is not particularly limited, and any organic solvent that is previously known to be suitable for electrolytes of lithium ion batteries, etc. can be used. Examples of such organic solvents include at least one selected from the group consisting of carbonate-based solvents, ether-based solvents, nitrile-based solvents, phosphate-based solvents, and sulfone-based solvents.
[0025] More specifically, carbonate-based solvents may include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, methylpropyl carbonate, ethylmethyl carbonate, ethylpropyl carbonate, methyl (2,2,2-trifluoroethyl) carbonate, etc. Phosphate-based solvents may include trimethyl phosphate, triethyl phosphate, 2-(2,2,2-trifluoroethoxy)-1,3,2-dioxaphosphorinane-2-oxide, etc.
[0026] In addition, as the ether solvent, dibutyl ether, tetraglyme, diglyme, dimethoxyethane or tetrahydrofuran derivatives such as 2-methyltetrahydrofuran can be used; as the nitrile solvent, succinonitrile, adiponitrile, sebaconitrile, acetonitrile, propionitrile, etc. can be used. In addition, as the sulfone solvent, dimethyl sulfone, ethyl methyl sulfone, cyclopentane sulfone, etc. can be used.
[0027] However, from the viewpoint of excellent mechanical properties and safety of the composite electrolyte, as the organic solvent, it is preferred to use a carbonate solvent, a sulfone solvent, a phosphate solvent, etc. that can be at least partially cured together with the cross-linked polymer and exhibit flame retardancy. In addition, as the organic solvent, it is more preferred to use a solvent that exhibits low volatility under the curing conditions for forming the cross-linked polymer, for example, under a heat curing condition of 60 to 80°C.
[0028] On the other hand, the lithium salt dissolved or dispersed in the organic solvent may include any lithium salt previously known to be suitable for use in an electrolyte for a lithium secondary battery, such as at least one selected from the group consisting of LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiCl, LiBr, LiI, LiClO4, LiBF4, LiPF6, LiB 10 Cl 10 , LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (C2F5SO2)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium lower aliphatic carboxylates having less than 4 carbon atoms, lithium 4-phenylborate and lithium imide.
[0029] Such a lithium salt may be included in the organic solvent of the liquid electrolyte at a concentration of 0.8 M to 4.0 M, or 1.0 M to 2.0 M, whereby the composite electrolyte of one embodiment can exhibit excellent thermal stability and ion conductivity.
[0030] On the other hand, the composite electrolyte of one embodiment includes a cross-linked polymer including the liquid electrolyte and oxide-based solid electrolyte particles in a cross-linked structure as described below. Such a cross-linked polymer may be a cross-linked polymer obtained by thermally curing a multifunctional monomer having a plurality of curable unsaturated bonds such as a (meth)acrylate group, an alkoxylate group, a hydroxyl group, a cyano group, or a carboxylic acid group.
[0031] Since the liquid electrolyte is contained in the cross-linked structure of such a cross-linked polymer, the composite electrolyte exhibits excellent mechanical properties even without a separate separation membrane, and can further improve the safety of the lithium secondary battery by suppressing liquid leakage.
[0032] More specific examples of the curable monomer for forming the crosslinked polymer include at least one selected from the group consisting of ethylene glycol diacrylate, triethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate, bisphenol A ethoxylated dimethacrylate, acrylic acid, carboxyethyl acrylate, methyl cyanoacrylate, ethyl cyanoacrylate, ethyl cyanoethoxyacrylate, cyanoacrylic acid, hydroxyethyl methacrylate, and hydroxypropyl acrylate. It goes without saying that the crosslinked polymer may be a homopolymer in which one selected from these substances is cured or a copolymer in which two or more of them are cured.
[0033] Based on the total weight of the composite electrolyte, the content of such a cross-linked polymer may be 3 wt % to 20 wt %, or 5 wt % to 15 wt %. Therefore, the composite electrolyte of one embodiment may exhibit more excellent mechanical properties, so that liquid leakage, etc. may be more effectively suppressed, and the liquid electrolyte and the oxide-based solid electrolyte particles are also uniformly contained and dispersed on the cross-linked polymer, thereby exhibiting further improved ion conductivity.
[0034] On the other hand, the composite electrolyte of one embodiment has a particle size of more than 300 nm, or 310 nm to 800 nm, or 350 nm to 600 nm, so as to exhibit further improved ion conductivity, and further includes oxide-based solid electrolyte particles dispersed on the cross-linked polymer.
[0035] In particular, as supported by the following examples, it is confirmed that when the particle size range and / or content range of such oxide-based solid electrolyte particles are optimized, the composite electrolyte of one embodiment can exhibit improved ionic conductivity. On the other hand, it is confirmed that when the particle size range of the oxide-based solid electrolyte particles is reduced to below 300 nm, the ionic conductivity of the composite electrolyte deteriorates. In addition, even when the particle size range is too large, the oxide-based solid electrolyte particles may not be uniformly dispersed, which may deteriorate the performance of the composite electrolyte.
[0036] Such oxide-based solid electrolyte particles may include, for example, one or more lithium-containing oxide-based particles, the lithium-containing oxide-based particles being selected from the group consisting of LAGP (lithium aluminum germanium phosphate) compounds, LLZO (lithium lanthanum zirconium oxide) compounds, LATP (lithium aluminum titanium phosphate) compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) compounds, LSTP (lithium silicon titanium phosphate) compounds, and lithium oxides (e.g., Li2O). Among them, the cation transport coefficient can be further improved by using particles of LATP (lithium aluminum titanium phosphate) compounds, and the composite electrolyte of one embodiment can exhibit further improved ion conductivity.
[0037] In addition, based on 100 parts by weight of the total amount of the above-mentioned liquid electrolyte and the cross-linked polymer, the content of the oxide solid electrolyte particles can be 0.1 parts by weight to 15 parts by weight, or 0.3 parts by weight to 12 parts by weight. It has been confirmed that when the content of the oxide solid electrolyte particles is too small, the ion conductivity of the composite electrolyte is insufficient, and even when its content is too large, the ion conductivity of the composite electrolyte is reduced.
[0038] The composite electrolyte of one embodiment described above can be prepared by a method comprising the following steps: forming a composition on a substrate, the composition comprising a liquid electrolyte, a monomer having a curable functional group, and oxide-based solid electrolyte particles having a particle size greater than 300 nm; and thermally curing the monomer of the composition at above 60° C. or at 60° C. to 80° C. in the presence of an initiator.
[0039] According to the preparation method, a composite electrolyte of one embodiment showing excellent mechanical properties and ion conductivity can be prepared by a simple method of mixing the components of the composite electrolyte of one embodiment in the presence of a thermal initiator, etc. and thermally curing the monomers. In addition, in the preparation method, since the composite electrolyte is prepared by thermal curing at a temperature of about 60° C. to 80° C., the phenomenon of evaporation of the organic solvent, etc. contained in the liquid electrolyte during the above preparation process can be reduced, and a composite electrolyte with better performance can be prepared.
[0040] On the other hand, according to an example of a method for preparing a composite electrolyte, the above-mentioned organic solvent and lithium salt are first mixed to form a liquid electrolyte, and a monomer having a curable functional group, oxide solid electrolyte particles with a particle size greater than 300 nm, a thermal initiator, etc. are simultaneously or sequentially added and mixed into the liquid electrolyte, and then this composition is coated on a substrate, heat treated and cured to prepare the above-mentioned composite electrolyte.
[0041] At this time, the curing process, etc. can be carried out on a separate porous separation membrane or a positive electrode or a negative electrode, or can be carried out on a separate substrate (e.g., a resin substrate such as polyester, such as PET) prepared in advance. Depending on the type of each substrate on which the curing process is carried out, the composite electrolyte is prepared in the form of coating on the separation membrane, coating and attaching to each electrode, or in the form of a self-supporting film itself, and can be used as an electrolyte membrane to replace the porous separation membrane of a lithium secondary battery.
[0042] Furthermore, the composition may be coated on a substrate according to a general liquid composition coating method, and the curing process may vary depending on the specific composition of the composition, but may be performed, for example, by heat treatment for 1 to 24 hours or 2 to 12 hours.
[0043] On the other hand, in order to properly heat cure the above-mentioned monomers, a thermal initiator previously known to be useful for curing or crosslinking polymerization of a multifunctional monomer having a (meth)acrylate group, an alkoxylate group, a hydroxyl group, a cyano group, a carboxylic acid group, etc. can be used as an initiator. Specific examples of such initiators include peroxide initiators such as benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, tert-butyl peroxy-2-ethylhexanoate, cumyl hydroperoxide, or hydrogen peroxide; or 2,2'-azobis(2-cyanobutane), 2,2'-azobis(methylbutyronitrile), 2,2'-azobis(isobutyronitrile) (AIBN), 2,2'-azobisdimethylvaleronitrile (AMVN), etc., and two or more selected from these substances can be used together, or various other thermal initiators can be used.
[0044] Meanwhile, according to another embodiment of the present disclosure, a lithium secondary battery comprising the composite electrolyte is provided. Such a lithium secondary battery includes, for example, a positive electrode containing a positive electrode active material; a negative electrode containing a negative electrode active material; and a composite electrolyte of one embodiment between the positive electrode and the negative electrode.
[0045] According to a more specific example, the included composite electrolyte is in the form of an outer coating film coated and attached to the positive electrode or the negative electrode (for example, see the battery embodiment 2 below), or alternatively, it is prepared in the form of a self-supporting film and is not attached to the positive electrode or the negative electrode, but the included composite electrolyte can be in the form of an electrolyte membrane that is detachably between the positive electrode and the negative electrode (for example, see the battery embodiment 1 below). In addition, such an electrolyte membrane can be included alone, however, it can further include a porous separation membrane between the positive electrode and the negative electrode together with the electrolyte membrane to provide additional mechanical properties and insulation properties of the lithium secondary battery. The electrolyte membrane can be laminated on this porous separation membrane.
[0046] On the other hand, in the lithium secondary batteries of other embodiments, the positive electrode active material is not particularly limited as long as it is a material that can reversibly embed and deintercalate lithium ions, and examples thereof may include lithium metal composite oxides containing one or more metal elements selected from the group consisting of Co, Mn, Ni, W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg and Mo.
[0047] More specifically, as the positive electrode active material, a compound represented by any one of the following formulae may be used. a A 1- b R b D2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Li a E1-b R b O 2-c D c (where 0.90≤a≤1.8, 0≤b≤0.5, and 0≤c≤0.05); LiE 2-b R b O 4-c D c (where 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b R c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Co b R c O 2-α Z α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Co b R c O 2-α Z2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b-c Mn b R c D α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α≤2); Li a Ni 1-b-c Mn b R c O 2-α Z α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni 1-b- c Mn b R c O 2-α Z2 (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05 and 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5 and 0.001≤d≤0.1); Li aNi b Co c Mn d G e O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5 and 0.001≤e≤0.1); Li a NeG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a MnG b O2 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn b O4 (where 0.90≤a≤1.8 and 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; and Li (3-f) J2(PO4)3(0≤f≤2).
[0048] In the above formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, V or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.
[0049] In addition, in addition to the above-mentioned positive electrode active material, the positive electrode may also include a binder and a conductive material. The binder is a component that helps the bonding between the positive electrode active material and the conductive material and the bonding with the collector, and may be, for example, selected from the group consisting of polyvinylidene fluoride (PVdF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF / HFP), polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, polymethyl (meth) acrylate, polyethyl (meth) acrylate, polytetrafluoroethylene (PTFE), polyvinyl chloride, polyacrylonitrile, polyvinyl pyridine, polyvinyl pyrrolidone, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butylene rubber, fluororubber, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose and mixtures thereof, but are not necessarily limited thereto.
[0050] The binder may be added in an amount of 1 to 50 parts by weight, or 3 to 15 parts by weight, based on 100 parts by weight of the total weight of the positive electrode. As a result, excellent adhesion between the positive electrode active material and the collector and capacity characteristics of the secondary battery can be maintained.
[0051] In addition, the conductive material contained in the positive electrode is not particularly limited as long as it does not cause side reactions in the internal environment of the battery and has excellent conductivity while not causing chemical changes in the battery. The conductive material can generally be graphite or conductive carbon, and can be, for example, one selected from the group consisting of: graphite, such as natural graphite or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, Denka black, thermal black, channel black, furnace black and lamp black; a carbon-based material having a crystal structure of graphene or graphite; conductive fibers, such as carbon fibers and metal fibers; carbon fluoride; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive oxides, such as titanium oxide; conductive polymers, such as polyphenylene derivatives; or mixtures of two or more thereof, but are not necessarily limited thereto.
[0052] The conductive material may be added in an amount of 0.5 to 50 parts by weight, or 1 to 30 parts by weight, based on 100 parts by weight of the total weight of the positive electrode, thereby maintaining the excellent electrochemical properties of the positive electrode and the lithium secondary battery, such as conductivity and capacity.
[0053] In addition, a filler may be optionally added to the positive electrode as a component for suppressing the expansion of the positive electrode. Such a filler is not particularly limited as long as it can suppress the expansion of the electrode without causing chemical changes in the battery, and examples thereof may include: olefin polymers such as polyethylene and polypropylene; fiber materials such as glass fiber and carbon fiber.
[0054] The positive electrode can be prepared, for example, by dispersing and mixing a positive electrode active material, a binder, a conductive material, etc. in a dispersion medium (solvent) to form a slurry, applying the slurry to a positive electrode collector, and then drying and rolling it. At this time, the dispersion medium may be N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, isopropanol, water, or a mixture thereof, but is not necessarily limited thereto.
[0055] In addition, the positive electrode collector can be platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), aluminum (Al), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), ITO (In doped SnO2), FTO (F doped SnO2) or its alloy, or aluminum (Al) or stainless steel whose surface is treated with carbon (C), nickel (Ni), titanium (Ti) or silver (Ag), etc. The positive electrode collector can be in the form of foil, film, sheet, stamping body, porous body, foam, etc.
[0056] In addition, in the lithium secondary battery of another embodiment described above, the negative electrode can be prepared according to conventional methods known in the art. For example, the negative electrode active material, the conductive material, the binder and the filler, if necessary, are dispersed and mixed in a dispersion medium (solvent) to form a slurry, and the slurry can be applied to the negative electrode collector, which is then dried and rolled to prepare the negative electrode.
[0057] At this time, as the negative electrode active material, a compound capable of reversibly inserting and deinserting lithium can be used. Specific examples of the negative electrode active material may be: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber or amorphous carbon; metal materials capable of alloying with lithium, such as Si, Al, Sn, Pb, Sb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy or Al alloy; metal oxides capable of doping and dedoping lithium, such as SiO β (0<β<2), SnO2, vanadium oxide or lithium vanadium oxide; alternatively, a composite material comprising a metal material and a carbonaceous material, such as a Si-C composite material or a Sn-C composite material, and any one of them or a mixture of two or more thereof can be used. In addition, as a negative electrode active material, a metallic lithium film can be used. In addition, as a carbonaceous material, low-crystalline carbon and high-crystalline carbon can be used. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-type, flake-type, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-type carbon fibers, mesophase carbon microbeads, mesophase pitch and high-temperature calcined carbon such as coke derived from petroleum or coal tar pitch.
[0058] In addition, since the binder and the conductive material are the same as those in the above-mentioned positive electrode, further description thereof will be omitted.
[0059] The negative electrode collector can be platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), copper (Cu), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), ITO (In doped SnO2), FTO (F doped SnO2) or its alloy, or copper (Cu) or stainless steel treated with carbon (C), nickel (Ni), titanium (Ti), silver (Ag) and the like on the surface, but not necessarily limited thereto. The negative electrode collector can be in the form of foil, film, sheet, stamping body, porous body, foam and the like.
[0060] On the other hand, in the lithium secondary battery of another embodiment, the composite electrolyte of one embodiment can be in the form of a film or film with a layered structure as described above, for example, between the positive electrode and the negative electrode. In this case, the composite electrolyte membrane can also be used as a separator (that is, the positive electrode and the negative electrode are electrically insulated and lithium ions are also allowed to pass). At this time, the composite electrolyte membrane can be coated and attached to a surface of the positive electrode or the negative electrode in the form of a film, and is included in the secondary battery. In addition, the composite electrolyte membrane can be independently between the positive electrode and the negative electrode. In addition, the lithium secondary battery of other embodiments can be a semi-solid battery used in combination with a liquid electrolyte and a solid electrolyte.
[0061] In addition, when a porous separation membrane is added to a lithium secondary battery, such a separation membrane can be made of olefin polymers such as polyethylene and polypropylene or glass fiber in the form of sheets, multilayer films, microporous membranes, woven fabrics and nonwoven fabrics, but is not necessarily limited thereto. However, it is preferred to use porous polyethylene or porous glass fiber nonwoven fabrics (glass filters) as separation membranes, and more preferably use porous glass filters (glass fiber nonwoven fabrics) as separation membranes. The separation membrane can be an insulating film with high ion permeability and mechanical strength, and the pore size of the separation membrane can generally be in the range of 0.01 to 10 μm, and the thickness can generally be in the range of 5 to 300 μm, but is not limited thereto.
[0062] Meanwhile, the lithium secondary batteries of other embodiments can be prepared according to conventional methods in the art, for example, by forming a composite electrolyte membrane between a positive electrode and a negative electrode, and optionally adding a porous separation membrane.
[0063] Such a lithium secondary battery can be used not only as a battery cell used as a power source for small devices but also as a unit cell of a battery module used as a power source for medium- to large-sized devices.
[0064] [Beneficial Effects]
[0065] According to the present disclosure, since the liquid electrolyte is contained in the cross-linked structure of the cross-linked polymer, it can exhibit excellent mechanical characteristics even without a separate separation membrane, which provides a composite electrolyte that can minimize the occurrence of fire due to leakage of the liquid electrolyte, etc.
[0066] Furthermore, such composite electrolytes may exhibit improved ionic conductivity and may greatly contribute to improving the safety and electrical characteristics of lithium secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1a and 1b It shows the surface state of the positive electrode before the composite electrolyte of Example 2 is coated on the positive electrode during the preparation process of Battery Example 2 ( Figure 1a ) and the surface condition after external coating ( Figure 1b ) in comparison photos. DETAILED DESCRIPTION
[0068] The following embodiments will be described more fully below so that the present disclosure can be easily understood, but these embodiments are only for illustrative purposes. It will be apparent to those skilled in the art that various changes and modifications can be made within the scope of the present invention and the technical spirit, and it goes without saying that these changes and modifications fall within the scope of the appended claims.
[0069] Comparative Example 1: Preparation of composite electrolyte
[0070] First, a mixed solvent in which ethylene carbonate and propylene carbonate are mixed at a volume ratio of 1:1 is used as a non-aqueous organic solvent, and a lithium salt LiPF6 is dissolved therein at a concentration of 1 M to form a liquid electrolyte. This liquid electrolyte and ethoxylated trimethylolpropane triacrylate (ETPTA) as a monomer having a curable functional group are mixed at a weight ratio of 90:10, and based on 100 parts by weight of the mixture, 0.1 parts by weight of AIBN as a thermal initiator is further mixed to prepare a composition for forming a composite electrolyte.
[0071] The composition was coated on a PET substrate using a bar coater and heat-treated at 60° C. for 360 minutes for thermal curing. Thus, a composite electrolyte of Comparative Example 1 formed on a substrate was prepared.
[0072] Example 1: Preparation of composite electrolyte
[0073] In the preparation method of Comparative Example 1, the process of mixing the liquid electrolyte and the monomer having a curable functional group was performed in the same manner. In addition, 0.1 parts by weight of AIBN as a thermal initiator and 4 parts by weight of LiAl having a particle size of 400 nm were mixed based on 100 parts by weight of the mixture. 0.3Ti 1.7 (PO4)3 (LATP type) oxide solid electrolyte particles (weight ratio of liquid electrolyte + monomer: oxide particles = 25:1) to prepare a composition for forming a composite electrolyte.
[0074] The subsequent thermal curing process was performed in the same manner as in Comparative Example 1 to prepare a composite electrolyte of Example 1.
[0075] Example 2: Preparation of composite electrolyte
[0076] In the preparation method of Comparative Example 1, the process of mixing the liquid electrolyte and the monomer having a curable functional group was performed in the same manner. In addition, 0.1 parts by weight of AIBN as a thermal initiator and 11.1 parts by weight of LiAl having a particle size of 400 nm were mixed based on 100 parts by weight of the mixture. 0.3 Ti 1.7 (PO4)3 (LATP type) oxide solid electrolyte particles (weight ratio of liquid electrolyte + monomer: oxide particles = 9:1) to prepare a composition for forming a composite electrolyte.
[0077] The subsequent thermal curing process was performed in the same manner as in Comparative Example 1 to prepare a composite electrolyte of Example 2.
[0078] Example 3: Preparation of composite electrolyte
[0079] In the preparation method of Comparative Example 1, the process of mixing the liquid electrolyte and the monomer having a curable functional group is performed in the same manner. In addition, based on 100 parts by weight of the mixture, 0.1 parts by weight of AIBN as a thermal initiator and 4 parts by weight of lithium oxide (Li2O) oxide-based solid electrolyte particles having a particle size of 310 nm are mixed (the weight ratio of liquid electrolyte + monomer: oxide-based particles = 25:1) to prepare a composition for forming a composite electrolyte.
[0080] The subsequent thermal curing process was performed in the same manner as in Comparative Example 1 to prepare a composite electrolyte of Example 3.
[0081] Example 4: Preparation of composite electrolyte
[0082] In the preparation method of Comparative Example 1, the process of mixing the liquid electrolyte and the monomer having a curable functional group is performed in the same manner. In addition, based on 100 parts by weight of the mixture, 0.1 parts by weight of AIBN as a thermal initiator and 11.1 parts by weight of lithium oxide (Li2O) oxide-based solid electrolyte particles having a particle size of 310 nm are mixed (the weight ratio of liquid electrolyte + monomer: oxide-based particles = 9:1) to prepare a composition for forming a composite electrolyte.
[0083] The subsequent thermal curing process was performed in the same manner as in Comparative Example 1 to prepare a composite electrolyte of Example 4.
[0084] Comparative Example 2: Preparation of composite electrolyte
[0085] The composite electrolyte of Comparative Example 2 was prepared in the same manner as in Example 2, except that oxide-based solid electrolyte particles with a particle size of 200 nm and having the same chemical formula were used instead of LiAl with a particle size of 400 nm in the preparation method of Example 2. 0.3 Ti 1.7 (PO4)3 (LATP type) oxide solid electrolyte particles.
[0086] Comparative Example 3: Preparation of composite electrolyte
[0087] In the preparation method of Comparative Example 1, the process of mixing the liquid electrolyte and the monomer having a curable functional group was performed in the same manner. In addition, 0.1 parts by weight of AIBN as a thermal initiator and 25 parts by weight of LiAl having a particle size of 200 nm were mixed based on 100 parts by weight of the mixture. 0.3 Ti 1.7 (PO4)3 (LATP type) oxide solid electrolyte particles (weight ratio of liquid electrolyte + monomer: oxide particles = 8:2) to prepare a composition for forming a composite electrolyte.
[0088] The subsequent thermal curing process was performed in the same manner as in Comparative Example 1 to prepare a composite electrolyte of Comparative Example 3.
[0089] Comparative Example 4: Preparation of composite electrolyte
[0090] In the preparation method of Comparative Example 1, the process of mixing the liquid electrolyte and the monomer having a curable functional group was performed in the same manner. In addition, 0.1 parts by weight of AIBN as a thermal initiator and 42.86 parts by weight of LiAl having a particle size of 200 nm were mixed based on 100 parts by weight of the mixture. 0.3 Ti 1.7 (PO4)3 (LATP type) oxide solid electrolyte particles (weight ratio of liquid electrolyte + monomer: oxide particles = 7:3) to prepare a composition for forming a composite electrolyte.
[0091] The subsequent thermal curing process was performed in the same manner as in Comparative Example 1 to prepare a composite electrolyte of Comparative Example 4.
[0092] Battery Example 1: Production of Lithium Secondary Batteries
[0093] First, lithium nickel cobalt manganese composite oxide (NCM 811) containing 80 mol% nickel in all transition metals is used as a positive electrode active material. This positive electrode active material, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder are mixed in a weight ratio of 96.5:1.5:2, and the mixture is dispersed in an NMP solvent to prepare a slurry, and then a Matis coater (Labdryer / coater type LTE, Werner Mathis AG) as a scraper coater is used to coat a 25 μm thick aluminum foil (Al foil) to a uniform thickness, and dried in a vacuum oven at 120 ° C for 13 hours to manufacture a positive electrode for a lithium secondary battery.
[0094] A negative electrode for a lithium secondary battery was manufactured in the same manner as the above-mentioned positive electrode by using graphite as a negative electrode active material.
[0095] The positive electrode and the negative electrode were positioned to face each other, and the composite electrolyte membrane produced in the example or the comparative example was inserted between these electrodes to prepare an electrode assembly. The electrode assembly was placed in a case to produce a lithium secondary battery.
[0096] Battery Example 2: Production of Lithium Secondary Batteries
[0097] First, lithium nickel cobalt manganese composite oxide (NCM 811) containing 80 mol% nickel in all transition metals is used as a positive electrode active material. This positive electrode active material, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder are mixed in a weight ratio of 96.5:1.5:2, and the mixture is dispersed in an NMP solvent to prepare a slurry, and then a Matis coater (Labdryer / coater type LTE, Werner Mathis AG) as a scraper coater is used to coat a 25 μm thick aluminum foil (Al foil) to a uniform thickness, and dried in a vacuum oven at 120 ° C for 13 hours to manufacture a positive electrode for a lithium secondary battery.
[0098] A negative electrode for a lithium secondary battery was manufactured in the same manner as the above-mentioned positive electrode by using graphite as a negative electrode active material.
[0099] The composition for forming a composite electrolyte of Example 2 was coated on the positive electrode, and then the positive electrode was subjected to a heat curing treatment under the same conditions as in Comparative Example 1. As a result, the composite electrolyte of Example 2 was prepared in a state where the composite electrolyte was externally coated on the positive electrode. For reference, Figure 1a and 1b Photographs showing the surface state of the positive electrode before coating with the composition for forming a composite electrolyte and the surface state of the positive electrode externally coated with the composite electrolyte of Example 2 are respectively shown.
[0100] Then, the positive electrode and the negative electrode are positioned to face each other, and the composite electrolyte membrane or the porous polyethylene-based separation membrane manufactured in the example or comparative example is inserted between these electrodes to prepare an electrode assembly. The electrode assembly is placed in a case to produce a lithium secondary battery.
[0101] Experimental example: Measurement of ionic conductivity
[0102] The ionic conductivities of the composite electrolytes for lithium secondary batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were measured and the results are shown in the following Table 1. For measuring the ionic conductivity, SP-300otentiostat / Galvanostat (Bio-Logic SAS, France) was used as an AC impedance measuring instrument.
[0103] [Table 1]
[0104]
[0105] Referring to Table 1, it was confirmed that the composite electrolytes of Examples 1 to 4 exhibited excellent conductivity compared with Comparative Example 1 containing no oxide-based solid electrolyte particles and Comparative Examples 2 to 4 in which the particle size of the oxide-based solid electrolyte particles deviated from a certain level.
Claims
1. A composite electrolyte comprising: Liquid electrolytes; a cross-linked polymer of a monomer having a curable functional group; and Oxide-based solid electrolyte particles are dispersed on the cross-linked polymer and have a particle size greater than 300 nm.
2. The composite electrolyte according to claim 1, wherein The liquid electrolyte includes an organic solvent and a lithium salt.
3. The composite electrolyte according to claim 2, wherein The organic solvent includes at least one selected from the group consisting of carbonate solvents, ether solvents, nitrile solvents, sulfone solvents and phosphate solvents.
4. The composite electrolyte according to claim 1, wherein The monomer having a curable functional group includes at least one selected from the group consisting of ethylene glycol diacrylate, triethylene glycol diacrylate, ethoxylated trimethylolpropane triacrylate, bisphenol A ethoxylated dimethacrylate, acrylic acid, carboxyethyl acrylate, methyl cyanoacrylate, ethyl cyanoacrylate, ethyl cyanoethoxyacrylate, cyanoacrylic acid, hydroxyethyl methacrylate and hydroxypropyl acrylate.
5. The composite electrolyte according to claim 1, wherein The cross-linked polymer may be present in an amount of 3 wt % to 20 wt % based on the total weight of the composite electrolyte.
6. The composite electrolyte according to claim 1, wherein The particle size of the oxide solid electrolyte particles is 310 nm to 800 nm.
7. The composite electrolyte according to claim 1, wherein The oxide solid electrolyte particles include one or more particles selected from the group consisting of LAGP (lithium aluminum germanium phosphate) compounds, LLZO (lithium lanthanum zirconium oxide) compounds, LATP (lithium aluminum titanium phosphate) compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) compounds, LSTP (lithium silicon titanium phosphate) compounds and lithium oxide.
8. The composite electrolyte according to claim 1, wherein The content of the oxide-based solid electrolyte particles is 0.1 parts by weight to 15 parts by weight based on 100 parts by weight of the total amount of the liquid electrolyte and the cross-linked polymer.
9. A method for preparing the composite electrolyte according to claim 1, the method comprising the following steps: forming a composition on a substrate, the composition comprising a liquid electrolyte, a monomer having a curable functional group, and oxide-based solid electrolyte particles having a particle size greater than 300 nm; and The monomers of the composition are thermally cured at above 60°C in the presence of an initiator.
10. The method for preparing a composite electrolyte according to claim 9, wherein: The initiator is selected from the group consisting of benzoyl peroxide, acetyl peroxide, dilauryl peroxide, di-tert-butyl peroxide, tert-butyl peroxy-2-ethylhexanoate, cumyl hydroperoxide, hydrogen peroxide, 2,2'-azobis(2-cyanobutane), 2,2'-azobis(methylbutyronitrile), 2,2'-azobis(isobutyronitrile) (AIBN) and 2,2'-azobisdimethylvaleronitrile (AMVN).
11. A lithium secondary battery comprising: a positive electrode containing a positive electrode active material; a negative electrode comprising a negative electrode active material; and The composite electrolyte according to claim 1 is interposed between the positive electrode and the negative electrode.
12. The lithium secondary battery according to claim 11, wherein The composite electrolyte is coated on the positive electrode or the negative electrode.
13. The lithium secondary battery according to claim 11, wherein An electrolyte layer including the composite electrolyte is separably interposed between the positive electrode and the negative electrode. 14 . The lithium secondary battery according to claim 11 , further comprising a porous separation membrane interposed between the positive electrode and the negative electrode.
Citation Information
Cited By
Composite solid electrolyte diaphragm as well as preparation method and application thereof
CN120473664A
Composite solid electrolyte separator and preparation method and application thereof
CN120473664B
